Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

Isolation and Growth Characteristics of an EDTA-degrading Member of the α-subclass of Proteobacteria - Hans-Ueli Weilenmann; Barbara Engeli; Margarete Bucheli-Witschel; Thomas Egli (Biodegradation, 2004)